Interference management for LTE‐Advanced Het‐Nets: stochastic scheduling approach in frequency domain†. Issue 1 (12th September 2012) - Zheng, Zhong; Dowhuszko, Alexis A.; Hämäläinen, Jyri; Dammann, Armin; Plass, Simon; Fazel, Khaled
ABSTRACT Heterogeneous networks represent a practical way to face high traffic demands in densely populated areas. Nevertheless, to achieve these advertised data rates, advanced interference management techniques are required. Trying to tackle this problem, this paper presents a stochastic scheduling approach for two‐layer LTE‐Advanced networks. The proposed stochastic frequency‐domain scheduling (SFDS) algorithm seeks the avoidance of cross‐layer and colayer interference, and is based on allocating different portions of the transmission bandwidth probabilistically. The SFDS algorithm is first presented as an interference management solution for an orthogonal frequency‐division multiple access system (i.e. LTE‐Advanced downlink). Later on, the SFDS algorithm is extended to be compatible with single‐carrier frequency‐division multiple access transmissions, and its performance is evaluated when combined with open‐loop power control techniques (i.e. LTE‐Advanced uplink). Extensive system level simulations are carried out to evaluate the performance of SFDS algorithm in a predefined LTE‐Advanced scenario that combines both macrolayer and femtolayer. Results show that the proposed algorithm allows to balance the cross‐layer and colayer interferences, extending the performance trade‐offs that well‐known full‐range spectrum allocation and orthogonal spectrum allocation approaches provide. Copyright © 2012 John Wiley & Sons, Ltd.